The Effect of the Cooperative Learning Method (Student Team Learning) on Students’ Collaboration Skills in Islamic Education PAI at SMPN 2 Rengasdengklok - Hasna Fadlilatul Maula Hasna; Iqbal Amar Muzaki; Masykur H. Mansyur (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the effect of the cooperative learning method, Student Team Learning (STL), on the collaboration skills of seventh-grade students in Islamic Education at SMPN 2 Rengasdengklok. The research employed a quantitative correlational approach. The sample consisted of 40 students selected through simple random sampling. Data were collected using Likert-scale questionnaires and documentation, and analyzed using simple linear regression with SPSS version 25. The results indicate a positive and significant effect of STL on students’ collaboration skills, with a regression coefficient of 0.748 and a significance value of 0.000.